Mathematical Modeling with Two Strains to Investigate Evolution of COVID-19 from Computational and Theoretical Perspectives (European Journal of Pure and Applied Mathematics, 2025)
The respiratory disease COVID-19 is brought on by a mutagenic {ribonucleic acid (RNA)} virus. Variants with various traits that could potentially impact transmissibility started to appear globally in December 2020. We develop and examine a computational model of two-strain COVID-19 transmission behaviors in order to deal with this novel aspect of the disease. After a theoretical analysis, enough criteria are derived for the stability of the model's equilibrium. The model contains single-strain 1 and variant 2 endemic equilibria as well as disease-free and endemic equilibria. The global stability of the model equilibrium is demonstrated using the Lyapunov function. For each strain, we separately compute the basic reproductive numbers $\mathscr{R}_{01}
Keywords: $SEI_1I_2HRD$ model; Two strain model; NSFD scheme; COVID-19, Disease, Sensitivity Analysis, Stability Analysis and Reproduction Number.; Effective reproduction number; Fractional numerical analysis